Evaluation of business processes through process mining techniques - Sudmann, Hauke-Christian Uwe (2021)
The aim of this thesis is to evaluate the existing sales process of the financial technology start up ABC to develop suggestions for process improvements that are intended to lead to a reduction in overall through put time. For the evaluation, this thesis uses state-of-the-art process mining techniques, analyzes the common discovery algorithms, and determines the most suitable algorithm for ABC. The discovered process model is extended by performance data to identify bottlenecks and develop suggestions for their elimination. This thesis concludes that chosen process mining techniques are well suited to evaluate business processes of ABC and develop proposals for process redesign.